The Influence of Financial Literacy, Academic Achievement, and Organizational Experience on Entrepreneurial Intention Among Scholarship Students at the University of Lampung - Fitriansyah, Rahmat; Muslimin, Muslimin (CV. Kalimasada Group, 2025)
This study investigates the influence of financial literacy, academic achievement, and organizational experience on entrepreneurial intention among scholarship students at the University of Lampung. As traditional employment pathways grow increasingly uncertain, entrepreneurial development has emerged as a key strategy in higher education. A quantitative approach was employed using a structured questionnaire distributed to 135 scholarship recipients, with 57 valid responses analyzed. Multiple linear regression analysis revealed that financial literacy and organizational experience significantly affect entrepreneurial intention, while academic achievement does not show a significant impact. Financial literacy enhances students’ capacity for financial planning, investment decisions, and risk management, thereby strengthening entrepreneurial confidence. Organizational experience contributes to the development of soft skills such as leadership, networking, and decision-making, which are critical for entrepreneurship. The study highlights that practical skills and experiential learning hold greater influence than academic success alone in fostering entrepreneurial intention.